Longitudinal Shortening of the Left Ventricle by Cine-CMR for Assessment of Diastolic Function in Patients with Aortic Valve Disease - Ribeiro, Sergio Marrone; Azevedo Filho, Clerio Francisco De; Sampaio, Roney; Tarasoutchi, Flávio; Grinberg, Max; Kalil-filho, Roberto; Rochitte, Carlos Eduardo (Sociedade Brasileira de Cardiologia - SBC, 2019)
AbstractBackground: Diastolic dysfunction, commonly evaluated by echocardiography, is an important early finding in many cardiomyopathies. Cardiac magnetic resonance (CMR) often requires specialized sequences that extends the test time. Recently, feature-tracking imaging has been made available, but still requires expensive software and lacks clinical validation.Objective: To assess diastolic function in patients with aortic valve disease (AVD) and compare it with normal controls by evaluating left ventricular (LV) longitudinal displacement by CMR.Methods: We compared 26 AVD patients with 19 normal controls. Diastolic function was evaluated as LV longitudinal displacement in 4-chamber view cine-CMR images using steady state free precession (SSFP) sequence during the entire cardiac cycle with temporal resolution < 50 ms. The resulting plot of atrioventricular junction (AVJ) position versus time generated variables of AVJ motion. Significance level of p < 0.05 was used.Results: Maximum longitudinal displacement (0.12 vs. 0.17 cm), maximum velocity during early diastole (MVED, 0.6 vs. 1.4s-1), slope of the best-fit line of displacement in diastasis (VDS, 0.22 vs. 0.03s-1), and VDS/MVED ratio (0.35 vs. 0.02) were significantly reduced in AVD patients compared with controls, respectively. Aortic regurgitation showed significantly worse longitudinal LV shortening compared with aortic stenosis. Higher LV mass indicated worse diastolic dysfunction.Conclusions: A simple linear measurement detected significant differences on LV diastolic function between AVD patients and controls. LV mass was the only independent predictor of diastolic dysfunction in these patients. This method can help in the evaluation of diastolic dysfunction, improving cardiomyopathy detection by CMR, without prolonging exam time or depending on expensive software.

ResumoFundamentos: A disfunção diastólica, comumente avaliada por ecocardiografia, é um importante achado precoce na maioria das cardiomiopatias. A ressonância magnética cardíaca (RMC) frequentemente requer sequências específicas que prolongam o tempo de exame. Recentemente, métodos de imagens com monitoramento de dados (feature-tracking) foram desenvolvidos, mas ainda requerem softwares caros e carecem de validação clínica.Objetivos: Avaliar a função diastólica em pacientes com doença valvar aórtica (DVA) e compará-la a controles normais pela medida do deslocamento longitudinal do ventrículo esquerdo (VE) por RMC.Métodos: Nós comparamos 26 pacientes com DVA com 19 controles normais. A função diastólica foi avaliada como uma medida do deslocamento longitudinal do VE nas imagens de cine-RMC no plano quatro câmaras usando a sequência steady state free precession (SSFP) durante todo o ciclo cardíaco com resolução temporal < 50 ms. O gráfico resultante da posição da junção atrioventricular versus tempo gerou variáveis de movimento da junção atrioventricular. Utilizamos nível de significância de p < 0,005.Resultados: Deslocamento longitudinal máximo (0,12 vs. 0,17 cm), velocidade máxima em início de diástole (0,6 vs. 1,4s-1), velocidade máxima na diástase (0,22 vs. 0,03s-1) e a razão entre a velocidade máxima na diástase e a velocidade máxima em diástole inicial (0,35 vs. 0,02) foram significativamente menores nos pacientes com DVA em comparação aos controles normais, respectivamente. Pacientes com insuficiência aórtica apresentaram medidas de encurtamento longitudinal do VE significativamente piores em comparação aqueles com estenose aórtica. O aumento da massa ventricular esquerda indicou pior disfunção diastólica.Conclusões: Esta simples medida linear detectou diferenças significativas na função diastólica do VE entre pacientes com DVA e controles normais. A massa ventricular esquerda foi o único preditor independente de disfunção diastólica nesses pacientes. Este método pode auxiliar na avaliação da disfunção diastólica, melhorando a detecção de cardiomiopatias por RMC sem prolongar o tempo de exame ou depender de caros softwares.
Encurtamento Longitudinal do Ventrículo Esquerdo por Cine-RMC para Avaliação da Função Diastólica em Pacientes com Doença Valvar Aórtica
Keywords: Cardiovascular Diseases/mortality; Cardiomyopathy, Hypertrophic/complications; Diagnostic Imaging; Echocardiography; Magnetic Resonance Spectroscopy; Heart Failure; Aortic Valve Insufficiency; Doenças Cardiovasculares/mortalidade; Cardiomiopatia Hipertrófica/complicações; Diagnóstico por Imagem; Ecocardiografia; Espectroscopia por Ressonância Magnética; Insuficiência Cardíaca; Insuficiência da Valva Aórtica